(untitled) (IASH Indian Journal of Arid Horticulture, 2025)
The experiment was conducted during the year 2022-23 at the Department of Fruit Science, College of Horticulture and Forestry, Jhalrapatan, Jhalawar to investigate the effect of thiourea on growth and development of jackfruit cv. Chandra. The study consisted of nine treatments, arranged in a Randomized Block Design with three replications. Among the various treatments, the application of 2.0% Thiourea (T8 ) to individual plants was found to be significantly superior to the other treatments in terms of growth parameters, including plant height (17.84%), rootstock girth (21.82%), scion girth (21.34%), number of leaves per plant (26.55%), and leaf area (32.88%).